Environmental education, territoriality and interculturality, from the sustainable to the good living in latinoamérica - Ramírez, Liberio Victorino (Asuntos Económicos y Administrativos, 2013)
There have been recently known new theoretical proposals with a territorial and intercultural focusing and without qualifying development. What we mean with this, is that is not the market what has to be supported, neither the production, nor the economy; what it has to be sustainable and lasting, is the length of life. The world vision of one of the most important flows in Latinoamerica consists in this: the holistic and constructivist vision of the Red Nuevo Paradigma (Souza, Victorino 2010). The target of the present paper is to do a synthesis of the evolution of the theories about environmental education, territory, interculturality and development, throughout a document review, from the most traditional theories such as the environmental education to preserve even the most recent, about environmental education to sustainability, including ingredients such as the integral endogenous development and for ‘the good living’, from the latinoamerican perspective to build a political and educative proposal based on the environmental education for the sustainability in the superior education, in the intercultural context with a territorial focusing.